Challenges to implement carrying capacity framework: A case study of Pulau Perhentian Marine Park institutional framework - Mohd Nasir, Nadia; Ibrahim, Mansor; Mahamod, Lukman Hakim; Othman, Rashidi (Malaysian Institute of Planners (MIP), 2017)
The environmental quality at Pulau Perhentian Marine Park is degrading day by day. Many studies have been done in order to support sustaining the tourist sites such as having limits in development and tourist arrival,or better known as carrying capacity. Despite the existence of many agencies whose jobscope is related to Pulau Perhentian,poor implementation of the guideline is resulting in degrading environmental quality of the park.This paper looks at the roles and functionsof each government agencies related toPulau Perhentian. The outcome of this paper is the analysis of the current roles and responsibilities of the agenciesand where are the gaps that can be filled in order to promote sustainable tourism in Pulau Perhentian.